Radiation Priming Chimeric Antigen Receptor T-Cell Therapy in Relapsed/Refractory Diffuse Large B-Cell Lymphoma With High Tumor Burden. Issue 1 (January 2020) - Qu, Changju; Ping, Nana; Kang, Liqing; Liu, Hailing; Qin, Songbin; Wu, Qian; Chen, Xiaochen; Zhou, Meng; Xia, Fan; Ye, Aihua; Kong, Danqing; Li, Caixia; et al.
Abstract : Chimeric antigen receptor T-cell (CAR-T) therapy demonstrates impressive efficacy in relapsed/refractory (R/R) diffuse large B-cell lymphoma (DLBCL). However, CAR-T therapy–related severe cytokine release syndrome and neurological toxicity limit its clinical application in R/R DLBCL patients with high tumor burden. Here, we conducted a phase II clinical trial testing the efficacy and toxicities of CAR-T therapy in R/R non-Hodgkin lymphoma patients (NCT03196830). Among the enrolled patients, 10 R/R DLBCL patients with high tumor burden were analyzed. Before CAR-T therapy, 4 were treated with intensive combined chemotherapy (C-CAR-cohort), and 6 were exposed to radiotherapy (R-CAR-cohort). Patients in the R-CAR-T-cohort showed a higher overall response rate (100% vs. 25%, P =0.033) and less severe cytokine release syndrome (0% vs. 100%, P =0.0048) and neurotoxicity (0% vs. 75%, P =0.033) incidences than patients in the C-CAR-T-cohort. Furthermore, one case who responded to CAR-T therapy initially and who suffered a relapse shortly was exposed to radiation and achieved complete remission, with an increase in the number of CAR-T copies detected. This study demonstrates that radiotherapy is an optimal debulking regimen to managing R/R DLBCL patients before CAR-T therapy and a promising alternative salvage therapy for patients who suffer a relapse after CAR-T therapy by fuelling CAR-T copies.